The Effectiveness Of Implementing Parallel Investigations In Handling TPPU Cases Original From Forestry And Environmental Crimes - Kiki Kristanto; Joanita Jalianery; Fransisco; Heriamariaty (IAHN-TP Palangka Raya, 2024)
Parallel investigation is an investigation method carried out simultaneously by various law enforcement agencies in handling money laundering (TPPU) cases originating from forestry and environmental crimes. This study examines the effectiveness of implementing parallel investigations in this context, with the aim of identifying the advantages, challenges and impact of implementing this method on case handling. Overall, parallel investigation has proven to be an effective approach in handling TPPU cases originating from forestry and environmental crimes. This method is able to accelerate the investigation process, increase the accuracy of law enforcement, and support more comprehensive crime suppression, although it requires improvements in coordination and regulatory aspects.